Meristic and morphometric characters of small sandeel, Ammodytes tobianus L. (Actinopterygii: Ammodytidae), from the Gulf of GdaĹ„sk, Baltic Sea - B. Więcaszek; S. Krzykawski; A. Antoszek (Acta Ichthyologica et Piscatoria, 2007)
Background. The small sandeel, Ammodytes tobianus L., is a fish species of no commercial value, which is probably why its biology and, particularly, taxonomic status has not attracted much interest. However, the ecological importance of this species outweighs its economic value. It has been regarded a "vulnerable" fish species and therefore its taxonomic status urgently needs more detailed studies. The presently reported study was intended to be a contribution to the knowledge on poorly known morphology of this fish, from a single location in the southern Baltic Sea. Materials and methods. The fish (130 specimens, 9.2-16.3 cm TL) were collected in June 1995 from the area between the Puck Bay and open waters of the Gulf of GdaĹ„sk, at the depth of 8 m. Taxonomic analysis involved both meristic and morphometric characters. The lengths were expressed as percentage of the standard length (SL) of the fish while the fish head characters-as percentage of the head length (HL). In addition, the coefficients of correlation and determination (r and r2, respectively) were calculated for the relations between all characters studied and standard length (SL) and for the relations between the characters pertinent to head and the head length (HL) in the sample examined. The fish age was determined from the otoliths. Results. The age of fish examined ranged from 1+ to 4+, and the sandeels aged 2+ were the distinctly dominant age group. The most abundant size group was the 13.0-13.99 cm length class. The coefficients of variation in the meristic characters were relatively low. The vertebral count and the number of plicae were the most stable characters in the sample studied, while the anal- and pectoral fin ray counts proved to be the most variable ones. Meristic characters can be described by the formula: D (47-49) 50-55, P (10) 11-12 (13), A (24, 25) 26-30 (31), sp.br. (21) 22-27 (28), vt. 61-67 (68). The morphometric relations showed a tendency to allometry, only the postdorsal and postorbital distances showed almost the isometric pattern of growth. The head characters expressed as proportion of the head length showed a very low variability. The strongest negative relations, on the course of exponential curve, were recorded in the following characters: (first) depth of head, eye diameters, jaws length, interorbital distance (associated with the head length); (second) predorsal distance (associated with the fin arrangement), minimum and maximum body depths and length of caudal fin (the features associated with the body shape). Conclusion. The mean vertebral count obtained in the present study indicates the sampled sandeel from the Gulf of GdaĹ„sk to belong to the autumn-spawning component of the stock. The sandeel is a species of relatively short lifespan, the age group IV was the oldest one and the least numerous in the sample (3.38% of the all specimens). The head length and pectoral fin rays count may be regarded as the characters differentiating the Baltic and Atlantic populations, however more detailed study from different areas of the Baltic Sea is urgently needed to confirm this assumption.